The Role of Nociceptive Neurons in the Pathogenesis of Psoriasis - Zhang, Xuan; He, Yanling (Frontiers in Immunology, 2020)
Psoriasis is a chronic inflammatory skin disease. Emerging evidence shows that neurogenic inflammation, induced by nociceptive neurons and T helper 17 cells (Th17) responses, has a is fundamental in the role in maintenmaintainingance the of changes in the immune system due to psoriasis. immune alterations. NThe nociceptive neurons, specific primary sensory nerves, have a multi-faceted roles in detecting noxious stimuli, maintaining homeostasis, and regulating the immunity responses in the skin. Therefore, it is critical to understand the connections and interplay between the nociceptive neurons and the immune system in psoriasis. Here, we review works on the altered innervation that occurs in psoriasis. We examine how these distinct sensory neurons and their signal transducers participate in regulating inflammation. Numerous clinical studies reported the dysfunction of nociceptive neurons in psoriasis., Wwe discuss the mechanism under behind the unfaithful inconsistent activation ofn nociceptive neurons. Moreover, we review how neuropeptides, involved in regulating Th17 responses and the role of nociceptive neurons, regulate immunity in psoriasis. Understanding how nociceptive neurons regulate the immuneity responses enhances our knowledge of the neuroimmunitye involved in the pathogenesis of psoriasis and may form the basis for new approaches to treat psoriasisit.